ANALISIS FAKTOR PERKEBUNAN SAWIT TERHADAP EKSPOR MINYAK INDONESIA - Setianingsih; Jihad Lukis Panjawa (Transpublika Publisher, 2022)
This study's objective is to examine the factors that influence the quantity of oil exported from Indonesia, including the area of plantations, the price of palm oil, the exchange rate, and the amount of palm oil production. In the current study, Time Series data spanning the years 1989 to 2020 were subjected to an Error Correction Model (ECM) Test. This research was compiled using data from both the 2019-2021 National Leading Plantation Statistics book and the World Bank. In the near future, test results will be available. Price has a significant inverse relationship with Area, while Area has a significant positive relationship. Both of these connections are important. As indicated by a probability value of less than 5%, the exchange rate variable has a significant and negative relationship with the volume of palm oil exports in the long run, while the area variable has a significant and positive relationship with the volume of palm oil exports. Both of these connections are important.